Impact of climate policy uncertainty on corporate green investment: examining the moderating role of financing constraints - Song, Yingjie; Dong, Jie (Frontiers in Marine Science, 2024)
Corporate green investment is the key driver for achieving low-carbon transition and sustainable marine economy. Existing literature has identified several influencing factors of corporate green investment, but there is still limited research on the relationship between climate policy uncertainty and corporate green investment. To fill this gap, this paper innovatively explores the nonlinear impact of climate policy uncertainty on corporate green investment, simultaneously focuses on the moderating role of corporate financing constraints and analyzes the coastal characteristic heterogeneity. Using the sample of listed companies in China from 2014-2020, we find that climate policy uncertainty has an inverted U-shaped impact on corporate green investment. From the perspective of heterogeneity, the inverted U-shaped effect is more significant in coastal areas. Moderating effect test indicates that corporate financing constraints strengthen the inverted U-shaped relationship and shift the turning point of curve to the left. Additionally, we further find that climate policy uncertainty has an inverted U-shaped impact on environmental performance of companies in coastal areas through green investment. Our research will provide some potential insights for China’s climate policy making and corporate green transformation, so as to contribute to sustainable marine development.